Objective assessment of hormonal therapy value as the risk minimization method associated with the sex hormone deficit - N A Sheshukova; O V Bolshakova (IP Berlin A.V., 2014)
Modern views on the issue of menopausal hormone therapy based on updated recommendations of the International Menopause Society 2013 are reviewed in the following article as well as the basic principles of hormone therapy in peri - and postmenopausal women, its benefits and possible risks. An important emphasis is made on unequal undesirable consequences from the use of combined hormonal preparations, depending on their composition and, above all, progestin component.